Estudos de uma série de desemulsificantes e seus efeitos sobre a reologia de um tipo de óleo pesado - Bragança, Carlos (2009)
At petroleum industry, the formation and stability of emulsions of the type oil / water can trigger a series of problems ranging from production to refining. The main problems, caused by the presence of water are related to the processes of corrosion and stabilization of salts that can damage pipes and "poison" catalysts used in refining. Quantification of water in oil can be made by the Karl Fischer method, by dehydration or by the method of BSW (ASTM D4007). In the latter, used chemicals that act as demulsifiers, which may have greater or lesser power to "break" the emulsion, depending on the characteristics of the system. The withdrawal of water in oil (primary processing) may be made by physical processes such as electrostatic precipitation or by the use of chemical demulsifiers. However, little is known about the effect of such products in the production process, such as rheological factors, responsible for transporting the products from the place of production up to refining. In this work, it was studied the effectiveness of a series of demulsifiers on the stability of emulsions heavy oil / water solutions and the effects of solvents / demulsifiers on the rheology of a heavy oil with the objective of selecting the best product for use in both BSW tests as primary processing.